Application of Islamic Financial Governance in Sharia Banking in Indonesia - Mahyudin; Pebi Yolanda; Stephen Pwani (Yayasan Darussalam Bengkulu, 2023)
This research suggests a connection between Sharia banking and Sharia governance, particularly in Indonesia. The qualitative data for the study were gathered using the library approach. In this study, secondary data from books and articles on the subject that were gathered from reputable research publications were utilized. The necessity for Sharia banking services as well as the expanding diversity of products are what are driving the growth of the Sharia banking business. The findings of the literature research indicate that the Islamic banking sector must understand how popular it is becoming. All organizations under oppression need Islamic governance because it promotes and upholds Islamic banking and finance. The findings of this study suggest that Bank Indonesia laws control the application of Islamic Sharia in Indonesia. Indonesian Sharia banking must comply with Sharia principles and is governed by several laws and regulations about the conduct of transactions. However, Indonesian Islamic banks have not yet been able to incorporate Islamic governance into their day-to-day activities.